Advances and challenges in the clinical practice of respiratory tract pharmacology and pharmacotherapy - de Lacerda, Dhiego Alves; Lima, Larissa Luana Lopes; Honorato, Pedro Fechine; Vale, Renata Braga; das Neves, Diego Formiga; de Sá Filho, Claudenor Pinho; de Moura, Thiago Quirino; Figueiredo, Vinícius Costa; de Oliveira, Anaylle Vieira Lacerda; Isidório, Ubiraídys de Andrade (Revista Sistemática, 2024)
This paper addresses the advances and challenges in the clinical practice of respiratory tract pharmacology and pharmacotherapy. Respiratory pharmacology has evolved significantly, offering a wide range of medications for the treatment of conditions such as asthma and chronic obstructive pulmonary disease (COPD). Bronchodilators, inhaled corticosteroids, and risk factor modification strategies, such as smoking cessation, are key to improving lung function and reducing exacerbations.The use of modern drugs, as highlighted in "Goodman & Gilman's: The Pharmacological Basis of Therapeutics", is complemented by updated guidelines, such as those of the Global Initiative for Chronic Obstructive Lung Disease (GOLD) and the Brazilian Society of Pulmonology and Phthisiology. These guidelines aim not only to relieve symptoms but also to promote an integrated approach that improves patients' quality of life.Effective implementation of these strategies requires not only up-to-date scientific knowledge, but also public health policies that promote the rational use of medicines and educational interventions. Therefore, this study underscores the importance of a multidisciplinary approach to address the complex challenges associated with chronic respiratory diseases.